Plasma Levels of Matrix Metalloproteinases 2 and 9 in Patients with Chronic Chagas Heart Disease and Systemic Arterial Hypertension: Correlation with TGF-Beta Plasma Levels - Reinaldo B. Bestetti; Renata Dellalibera-Joviliano; Ellen Rizzi; Giselle F. Bonacio; Milton Faria-Jr; Rosemeire Furlan-Daniel; Suzeley Castro-França (Cardiology Research and Practice)
Background. Chronic Chagas heart disease (CCHD) and systemic arterial hypertension (SAH) frequently coexists in areas where Chagas disease is endemic. The effects of the association of both conditions (CCHD-SAH) on the extracellular matrix (ECM) remodeling are unknown. Matrix metalloproteinases (MMP) 2 and 9 are involved in ECM remodeling. The aim of this study was to evaluate MMP 2 and MMP9 in CCHD-SAH patients and to correlate their levels with those of the profibrogenic cytokine TGF-beta. Methods. We included 19 patients with CCHD-SAH, 14 patients with CCHD alone, and 19 controls matched by sex and age. MMP-2 and MMP-9 plasma levels were studied by gel zymography and showed as optical densities (OD). TGF-beta plasma levels were measured by double-ligand ELISA and expressed as pg/mL. Results. Median (5th, 95th) MMP-2 plasma levels were 1224.7 OD (1160, 1433.5) in patients with CCHD alone, 1424.1 OD (1267.5, 1561) in patients with CCHD-SAH, and 940 OD (898.1, 1000.8) in controls (p=0.001). MMP-9 plasma levels were 1870 OD (1740, 1904.1) in patients with CCHD alone, 1754.6 OD (1650, 2049) in those with CCHD-SAH and 89.7 OD (80, 96) in controls (p=0.0003). MMP-9 plasma levels were higher than those of MMP 2 in patients with CCHD-SAH (p=0.01). No correlation was found between TGF-beta plasma levels with MMP-2 serum levels (r = 0.12; p=0.7), but a moderate negative correlation (r = −0.46; p=0.048) was observed between TGF-beta and MMP-9 plasma levels. Conclusions. MMP-2 and especially MMP-9 may play a role in the ECM remodeling process in patients with CCHD-SAH. TGF-Beta may counteract the MMP effect on the ECM remodeling process in patients with CCHD-SAH.